2013
DOI: 10.1242/jeb.083238
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinity increases survival of freezing in the enchytraeidEnchytraeus albidus

Abstract: SUMMARYEnchytraeus albidus is a freeze-tolerant enchytraeid found in diverse habitats, ranging from supralittoral to terrestrial and spanning temperate to arctic regions. Its freeze tolerance is well known but the effect of salinity in this strategy is still poorly understood. We therefore studied the combined effect of salinity (0, 15, 35, 50‰ NaCl) and sub-zero temperatures (−5, −14, −20°C) on the freeze tolerance of E. albidus collected from two distinct geographical regions (Greenland and Germany). A full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These taxa are found more often in highly saline areas (figure 3), predominantly encountered at MM and ME (figure 2 a ); arachnids and tardigrades, on the other hand, tend to be more abundant in patches of nutrient-rich locations, predominantly at ME and LT (figures 2 a , 3 and 4). The observed habitat preferences for different invertebrate taxa are linked to substrate salinity, because salinity may affect soil biodiversity through constraining the amount of available food or by affecting physiological functions [10], such as freeze tolerance [64]. While most invertebrates are confined to low-saline substrates due to physiological constraints (here mostly LT), more halo-tolerant invertebrate taxa may be able to feed on halo-tolerant micro-eukaryotes in areas of high salinity [65].…”
Section: Discussionmentioning
confidence: 99%
“…These taxa are found more often in highly saline areas (figure 3), predominantly encountered at MM and ME (figure 2 a ); arachnids and tardigrades, on the other hand, tend to be more abundant in patches of nutrient-rich locations, predominantly at ME and LT (figures 2 a , 3 and 4). The observed habitat preferences for different invertebrate taxa are linked to substrate salinity, because salinity may affect soil biodiversity through constraining the amount of available food or by affecting physiological functions [10], such as freeze tolerance [64]. While most invertebrates are confined to low-saline substrates due to physiological constraints (here mostly LT), more halo-tolerant invertebrate taxa may be able to feed on halo-tolerant micro-eukaryotes in areas of high salinity [65].…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies (Fisker et al, 2014;Calderon et al, 2009) proposed that the mobilized glucose stores are also important as a fuel when the animals are frozen. An earlier study of freeze-tolerant oligochaetes (D. octaedra) found that the ability to survive winter frost correlates with the size of glycogen reserves , but for E. albidus the relationship between winter survival and accumulation of glucose is generally weak (Slotsbo et al, 2008;Silva et al, 2013;Fisker et al, 2014). Here, we investigated whether the energy used for metabolism during the different treatments is primarily correlated to catabolism of glucose/glycogen or lipids.…”
Section: Changes In Metabolic Energy Sources During Freezingmentioning
confidence: 95%
“…Previous studies on freezetolerant insects and vertebrates have also suggested that metabolism can remain (partially) aerobic during freezing (Voituron et al, 2002;Sinclair et al, 2004;Sinclair et al, 2013), while a study of the freeze-tolerant worm D. octaedra indicated that metabolism was a mixture of aerobic and (mostly) anaerobic metabolism (Calderon et al, 2009). In the case of E. albidus, the aerobic metabolism is likely to be dependent on the relatively low ice content found in this species at −5°C (Patrício Silva et al, 2013).…”
Section: Energetic Costs Of Constant Freezing and Repeated Freezingmentioning
confidence: 99%
See 1 more Smart Citation
“…it tolerates internal ice formation) and it has a broad geographical distribution. Populations originating from different environmental conditions (from temperate to arctic environments) are all freeze tolerant, but have markedly different cold tolerance when examined in common garden experiments (Fisker et al 2014a, b;Patrício Silva et al 2013;Slotsbo et al 2008). As other freeze-tolerant oligochaete species, E. albidus mobilize high concentrations of glucose during freezing, which acts as a cryoprotectant and as a fuel for metabolism during overwintering (Fisker et al 2014b;Slotsbo et al 2008).…”
Section: Introductionmentioning
confidence: 99%